On Some New Results in M-Fuzzy Metric Space - Bhandari, Thaneshwor; Pahari, Narayan (Butwal Campus Journal, 2020)
This paper concerns our sustained efforts for introduction of M-fuzzy metric spaces and study their basic topological properties by introducing the Generalized metric space. As an application of this concept, we prove some Convergences, Cauchy and continuous properties related in M-fuzzy metric space and introduce some related examples in support of our results.